Identifying Structural Breaks in Asset Pricing Behavior in the Indian Context - Raghuram, G.; Erickson, Christopher (Indian Journal of Finance, 2017)
The paper studied the asset pricing behavior in India for the time period from April 1991 till March 2015 by employing the Fama-French three factor model and discovered a structural break in November 2001. This structural break was due to the coefficient of the value factor that showed a statistically significant increase post break point. For all the six test portfolios considered, the market factor and size factor premiums had statistically significant coefficients throughout the study period. In the pre-break point period, four of the six portfolios had a statistically significant coefficient for the value factor premium, while for the post break point, all the six test portfolios had a statistically significant coefficient for the value factor premium. The evidence, therefore, pointed to an increasing importance for the value factor. The paper also provided evidence that the Fama-French three factor model is a good descriptor of returns in the Indian context. The discovery of the structural break in the asset pricing behavior was also consistent with the adaptive market hypothesis (AMH).